(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In given article the main factors and features of modern international confl icts are analyzed. Also, the reasons and forms of international confl icts of modern world are revealed. Authors defi ned an essence and character of international confl icts and their consequences were analyzed. Due to the change of characteristics and essence of international confl icts different ways of regulation and their decision were considered.